Towards an Islamic Self-Regulated Learning (I-SRL) Framework: Integrating Az-Zarnuji’s Epistemology with Contemporary Learning Theory: (Menuju Kerangka Islamic Self-Regulated Learning (I-SRL): Integrasi Epistemologi Az-Zarnuji dengan Teori Pembelajaran Kontemporer) - Rahmatul Husniah; Putri Desi Natalia; Siti Asisah; Ahsan Hakim (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2026)
Purpose: This study aims to analyze the integration of Self-Regulated Learning (SRL) theory with the epistemology of learning in Ta’lim al-Muta’allim by Burhan al-Islam Az-Zarnuji. Method: Employing a qualitative library research design with a comparative approach, this study examines relevant classical and contemporary literature through conceptual and thematic analysis to identify the epistemological convergence and distinction between SRL theory and Az-Zarnuji’s learning framework. Findings: The findings reveal that although SRL primarily emphasizes psychological and cognitive dimensions, while Ta’lim al-Muta’allim foregrounds spiritual and ethical dimensions, both frameworks converge on the significance of self-regulation, goal setting, and self-reflection in the learning process. Future Research: Therefore, this study proposes the Islamic Self-Regulated Learning (I-SRL) model as a conceptual framework that integrates SRL principles with Islamic values, including intention, adab, and the blessing of knowledge. Implications: Theoretically, this study contributes to the development of Islamic pedagogy by offering a learning model that combines cognitive-regulative strategies with spiritual and ethical orientations relevant to twenty-first-century education. Novelty: The novelty of this study lies in its synthesis of contemporary SRL theory and the classical Islamic educational thought of Az-Zarnuji into an integrative I-SRL model applicable to contemporary Islamic education contexts